III.3 The Problem ∇ · v = f 173
Remark III.3.6 Remark III.3.1 equally applies to Theorem III.3.1.
Remark III.3.7 Theorem III.3.1 leaves out the two limiting cases q = 1, ∞.
As a matter of fact, in both cases, problem (III.3.2) does not have a solution
for all f ∈ L
q
(Ω) satisfying (III.3.1). A pro of of this assertion when q = ∞, is
given by Preiss (1997), McMullen (1998, Theorem 2.1) and Bourgain & Brezis
(2002, §2.2); see also Dacorogna, Fusco & Tartar (2004). A proof of the non-
solvability of problem (III.3.2) when q = 1 for arbi trary f ∈ L
1
(Ω) satisfying
(III.3.1), can be found in Bourgain & Brezis (200 3, §2.1) and in Dacorogna,
Fusco & Tartar (2004). The argument of Bourgain & Brezis is elementary and
will be reproduced here. Thus, assume that the problem
∇ · v = f , kvk
1,1
≤ c kfk
1
(III.3.30)
has at least one solution v ∈ W
1,1
0
(Ω), corresponding to an arbitrarily given
f ∈ L
1
(Ω) satisfying (III.3.1). Choose f = g −g
Ω
, where g is any function in
L
1
(Ω), and let u ∈ C
∞
0
(Ω). From (III.3.30) we thus have
(∇u, v) = −(u, ∇· v) = −(u, g −g
Ω
) ,
which, by a simple calculation that uses the H¨older inequality and Theorem
II.3.2, implies
|(u − u
Ω
, g)| ≤ k∇uk
n
kvk
n/(n−1)
≤ c k ∇uk
n
kvk
1,1
.
From this latter relati on, from (III.3.30)
2
, and from Theorem II.2.2 we readily
deduce
ku − u
Ω
k
∞
= sup
g∈L
1
(Ω);kgk
1
=1
|(u − u
Ω
), g)| ≤ c k∇uk
n
,
which, by (II.2.6) and (II.5.1), in turn implies the following property
kuk
∞
≤ c k∇uk
n
, for all u ∈ C
∞
0
(Ω) ,
which, as we know from Exercise II.3.8, is not true .
Remark III.3.8 If q > n, in view of the embedding Theorem II.3.2, a ny
solution v to (III.3.1)–(III.3.2), belongs, in addition, to L
∞
(Ω).
6
Of course,
as we know from Exercise II.3.8, this embedding does not hold if q = n and,
therefore, we can not prove, in such a case, v ∈ L
∞
(Ω), at least by this kind
of argument. However, it is simple to bring examples where, for certain f
and Ω, it is indeed po ssible to produce a solution to (III.3.1)–(III.3.2) which
is in L
∞
(Ω), under the sole assumption that f ∈ L
n
(Ω). For instance, let
Ω = B
R
, for som e R > 0, and assume that f = f(|x|), f ∈ L
n
(B
R
). Then, by
a straightforward calculation, we prove that a solution to (III.3.1)–(III.3.2) is
given by
6
Actually, to C(Ω).